2015
DOI: 10.1007/s00405-015-3515-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic effects of So-Cheong-Ryong-Tang in ovalbumin-induced allergic rhinitis model

Abstract: Allergic rhinitis (AR) is an allergic inflammation of the nasal airways. The Korean herbal medicine, So-Cheong-Ryong-Tang (SCRT) has been typically used for the treatment of AR for hundreds of years. In the present study, we investigated whether SCRT suppresses the progression of AR in animal model. AR was induced by ovalbumin (OVA). Treatment with SCRT was assessed to study the effect of SCRT on AR in mice. Histological analysis, multiplex cytokine assay, blood analysis, cell viability assay, RT-PCR and Elisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…According to the OASIS, this mixture has long been used to treat common cold, bronchitis, and bronchial asthma in the traditional oriental clinic. It is an herbal mixture used to treat various diseases such as allergic rhinitis and asthma ( Yang et al, 2009 ; Wang et al, 2012 ; Kim et al, 2014 ; Ku et al, 2016 ). It was recently shown that So-Cheong-Ryoung-Tang effectively decreased the production of cytokines and chemokines on airway remodeling in allergic asthma model and attenuated allergic effects in a rat model of ovalbumin-induced rhinitis via the phosphatidylinositol 3 kinase (PI3K)/Akt signaling pathway ( Kim et al, 2014 ; Park et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the OASIS, this mixture has long been used to treat common cold, bronchitis, and bronchial asthma in the traditional oriental clinic. It is an herbal mixture used to treat various diseases such as allergic rhinitis and asthma ( Yang et al, 2009 ; Wang et al, 2012 ; Kim et al, 2014 ; Ku et al, 2016 ). It was recently shown that So-Cheong-Ryoung-Tang effectively decreased the production of cytokines and chemokines on airway remodeling in allergic asthma model and attenuated allergic effects in a rat model of ovalbumin-induced rhinitis via the phosphatidylinositol 3 kinase (PI3K)/Akt signaling pathway ( Kim et al, 2014 ; Park et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there exists one randomised clinical trial for SCRT use in patients with AR. 10 However, primary outcome measurement conducted in that study was not suitable to estimate sample size. We applied effect size and SD values obtained from other trials that used herbal medicines in patients with AR.…”
Section: Methods Study Designmentioning
confidence: 91%
“…SCRT has been observed to regulate cytokines in animal studies. [10][11][12] However, no clinical study has observed the effect of SCRT on cytokine regulation.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional Korean Medicine, several herbal medicines have been used for the treatment of allergic inflammation. Especially, Tonggyu-tang (TGT) composed of 12 herbs (Table 1), similarly Pyeongwee-San [7], Biyeom-Tang [8], Hyeonggaeyeongyo-Tang [9] and So-Cheon-Ryon-Tang [10] have shown anti-inflammatory effects on patients with allergic nasal disorder.…”
Section: Introductionmentioning
confidence: 99%